Transfer of Agricultural Technology - Chole, R.R; Deshmukh , P.R. (New Delhi Scientific publishers, 2010)
the book contains all important aspect of transfer of technology leading to building the required capability to transfer of agricultural technologies in the learner
communication programme planning teaching aids farm telecast
Keywords: communication , programme, planning, farm telecast